2008
DOI: 10.1371/journal.pone.0002380
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Temporal but Not Attentional Processing in Expert Tennis Players

Abstract: In tennis, as in many disciplines of sport, fine spatio-temporal resolution is required to reach optimal performance. While many studies on tennis have focused on anticipatory skills or decision making, fewer have investigated the underlying visual perception abilities. In this study, we used a battery of seven visual tests that allowed us to assess which kind of visual information processing is performed better by tennis players than other athletes (triathletes) and non-athletes. We found that certain time-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 36 publications
(53 reference statements)
4
39
0
1
Order By: Relevance
“…More specifically, it was claimed that athletes trained under both physical and cognitive loads show a larger modulatory effect on cognitive function than those trained under each individually (Chan, Wong, Liu, Yu, & Yan, 2011;Wang, Chang, Liang, Shih, et al, 2013). In line with this argument, Overney, Blanke, and Herzog (2008) found that tennis players showed superiority in temporal perceptual processing relative to both triathletes and non-athletes, suggesting sport-related cognitive skills benefit through training (e.g., temporal processing in tennis). Interestingly, Chaddock, Neider, Voss, Gaspar, and Kramer (2011) reported that athlete and non-athlete differences in processing speed relates to daily multitasking abilities, indicating that higher efficiency in basic information processing for athletes may improve their capacity to perform daily challenges.…”
Section: Introductionmentioning
confidence: 62%
“…More specifically, it was claimed that athletes trained under both physical and cognitive loads show a larger modulatory effect on cognitive function than those trained under each individually (Chan, Wong, Liu, Yu, & Yan, 2011;Wang, Chang, Liang, Shih, et al, 2013). In line with this argument, Overney, Blanke, and Herzog (2008) found that tennis players showed superiority in temporal perceptual processing relative to both triathletes and non-athletes, suggesting sport-related cognitive skills benefit through training (e.g., temporal processing in tennis). Interestingly, Chaddock, Neider, Voss, Gaspar, and Kramer (2011) reported that athlete and non-athlete differences in processing speed relates to daily multitasking abilities, indicating that higher efficiency in basic information processing for athletes may improve their capacity to perform daily challenges.…”
Section: Introductionmentioning
confidence: 62%
“…While future research may lead to better ways distinguishing the two views, they may alternatively show that the concept of an intrinsic local V1 network is a fuzzy one. Overney et al (2008) showed that expert tennis players detected tennis balls more accurately than non-players against tennis court background but not landscape background and the two groups were no different in basic perceptual processes, such as detecting coherent motion from random dot matrices and attentional blink. Our results are in line with this study emphasizing the importance of trainingrelated stimuli.…”
Section: Discussionmentioning
confidence: 90%
“…It is unlikely that expert-novice differences in our study are related to differences in attention systems themselves [17] but rather to the way these are used in the task of analysing body kinematics to predict a shot. We also suggest a strong link between action observation and attention, in that the intentional movements of other human beings can be compelling environmental cues for the direction of attention.…”
Section: Discussionmentioning
confidence: 94%